Implementation, challenges and opportunities in 8D BIM for safety and health of oil and gas industry (gas station) - Muhammad Muizzuddin Mukhtar (2022)
8-Dimension Building Information Modelling (8D BIM) is known as a modern technology used in the construction industry which works as a tool to manage the physical and functional characteristics in the form of digital representation for safety and health parameter. However, recent studies for 8D BIM show that the application and execution of this technology are still low for most sectors, including the oil and gas industry with the lack of current construction projects with BIM implementation and there are many safety requirements needed to design an oil and gas building. Therefore, this research paper aims to study the execution of 8D BIM for safety & health adoption, to analyse the implementation, challenges and opportunities of BIM in oil and gas industry and lastly to exhibit the 3D modelling of a gas station occupied with standard safety measurements. The significances of the study from this research paper are to ensure the increase of 8D BIM level for safety and health adoption for construction industry, to acknowledge readers especially organisations and individuals related to oil and gas industry in implementing BIM and lastly to give a systematic and well-organized 3D modelling using BIM software and tools. The literature review shows the evaluation of the previous study on 8D BIM. The survey questionnaire illustrates the analysis from 50 respondents using SPSS with three tests: frequency, chi-square, and cross-tabulation. 3D modelling of a gas station displays an oil and gas industry building. From the survey questionnaire, it is found that 52% of respondents agree that the safety and health in construction are low in Malaysia. The top 3 challenges in implementing 8D BIM are lack of enforcement, complex BIM software, and lack of training programs. 3D model of the gas station. The benefit of 8D BIM based on questionnaires is it can improve coordination and communication. The challenges and opportunities obtained from the result significantly impact the collaboration of training and software between the academic field and industry.